Effects of stent postdilatation during primary PCI for STEMI: Insights from coronary physiology and optical coherence tomography. Issue 7 (23rd April 2020) - Karamasis, Grigoris V.; Kalogeropoulos, Andreas S.; Gamma, Reto A.; Clesham, Gerald J.; Marco, Valeria; Tang, Kare H.; Jagathesan, Rohan; Sayer, Jeremy W.; Robinson, Nicholas M.; Kabir, Alamgir; Aggarwal, Rajesh K.; Kelly, Paul A.; et al.
Abstract: Objectives: This study aimed to assess the impact of stent optimization by NC‐balloon postdilatation (PD) during primary‐PCI for STEMI with the use of coronary physiology and intracoronary imaging. Methods: This was a prospective observational study (ClinicalTrials.gov :NCT02788396). Optical coherence tomography (OCT) and physiological measurements were performed immediately before and after PD with the operators blinded to all measurements. The index of microcirculatory resistance (IMR), coronary flow reserve (CFR) and fractional flow reserve (FFR) were measured. OCT analysis was performed for assessment of stent expansion, malapposition, in‐stent plaque‐thrombus prolapse (PTP) and stent‐edge dissections (SED). The change in IMR before and after PD as a measure of microvascular injury was the primary objective of the study. Results: Thirty‐two STEMI patients undergoing primary‐PCI had physiological measurements before and after PD. All patients received second‐generation DES (diameter 3.1 ± 0.5 mm, length 29.9 ± 10.7 mm) and postdilatation with NC‐balloons (diameter 3.6 ± 0.6 mm, inflation pressure 19.3 ± 2.0 atm). IMR (44.9 ± 25.6 vs. 48.8 ± 34.2, p  = 0.26) and CFR (1.60 ± 0.89 vs. 1.58 ± 0.71, p  = 0.87) did not change, while FFR increased after PD (0.91 ± 0.08 vs. 0.93 ± 0.06, p  = 0.037). At an individual patient level, IMR increased in half of the cases. PD improved significantly absolute and relative stent expansion, reduced malapposition, and increased PTP. There was no difference in clinically relevant SED. Conclusion: In this exploratory, hypothesis‐generating study, postdilatation during primary‐PCI for STEMI improved stent expansion, apposition and post‐PCI FFR, without a significant effect on coronary microcirculation overall. Nevertheless, IMR increased in a group of patients and larger studies are warranted to explore predictors of microcirculatory response to postdilatation.